(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2021)
Objectives: The aim was to identify the benefits of using Dialkyl Carbamoyl Chloride for the treatment of biofilms in wounds. Methods: This is an integrative literature review that aimed to answer the guiding question: “What are the benefits of using Dialkyl Carbamoyl Chloride in the healing of skin lesions?”. The article selection stages resulted in 13 articles included. Results: The selected articles were grouped into two groups, namely: prevention and treatment of infection in wounds and prevention of surgical site infection, with nine productions in the first group and four in the second. Studies have shown that Dialkyl Carbamoyl Chloride attenuates colonization symptoms, such as odor, pain complaints and oozing, in addition to aiding in the prophylactic management of wound biofilm. Evidence indicates that dressings with Dialkyl Carbamoyl Chloride have no adverse effects, making them viable and safe options for chronic, acute and, mainly, infected injuries. Conclusion: It was identified that Dialkyl Carbamoyl Chloride was able to promote beneficial actions in the treatment of wounds, especially those of greater complexity. The proper choice of dressings and coverings can contribute to the rational use of existing technologies and antimicrobials, culminating in cost reduction and promotion of quality of life for individuals with chronic wounds.